(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article provides an overview of contemporary concerns within puppet theatre, including the importance of practice as research, autobiographical work and extensions of rehearsal techniques and processes; interdisciplinary contexts for puppetry, applied puppetry and the widening perspectives of intercultural studies, including the need for more detailed analyses of non-European forms. The article also highlights the role of the UNIMA Research Commission in pursuing the objectives of contemporary puppetry research. Keywords: Puppetry. Research. Interdisciplinary.